STRATEGY OF DEVELOPMENT OF AGRICULTURE OF UZBEKISTAN TO INCREASE INTERNATIONAL COMPETITIVENESS - Gulyamov S.S; Baymirzaev K.M; Zakhidov G.E.; Salmetova U.H (Scholar Express Journals, 2025)
Recently, after the currency liberalization of the Uzbek national currency, farmers have gained the right to directly participate in the sale of their products abroad. In order to compete in the international market it is necessary not only to find a buyer, but also to meet international ISO standards of product quality. This requires additional knowledge on product quality, for this purpose the department staff includes in the lesson plan seminars for farmers on product standardization
Keywords: competitiveness; certification; international standard